2019
DOI: 10.1002/cncr.32430
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and breast cancer screening: Cross‐sectional survey results from the behavioral risk factor surveillance system

Abstract: Background Postmenopausal obese women demonstrate an elevated breast cancer risk and experience increased breast cancer morbidity and mortality compared with women with a normal body mass index (BMI). However, to the authors' knowledge, prior studies have yielded inconclusive results regarding the effects of obesity on mammography screening adherence. Using national cross‐sectional survey data, the objective of the current study was to assess the current association between increasing BMI and use of mammograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In addition, before hospitalization, patients with and without obesity were equally nonadherent to BRC/CRC outpatient screening. This finding was consistent for BRC/CRC screening in larger studies, noting no differences in adherence between women with and without obesity [35][36][37] ; however, past studies have found morbidly obese Whites, low household income, and tobacco use to be risk factors for nonadherence to mammograms. 5,14,15,31 Furthermore, Denberg and colleagues found that lack of scheduled appointments, female sex, and type of insurance predicted nonadherence to screening colonoscopies.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, before hospitalization, patients with and without obesity were equally nonadherent to BRC/CRC outpatient screening. This finding was consistent for BRC/CRC screening in larger studies, noting no differences in adherence between women with and without obesity [35][36][37] ; however, past studies have found morbidly obese Whites, low household income, and tobacco use to be risk factors for nonadherence to mammograms. 5,14,15,31 Furthermore, Denberg and colleagues found that lack of scheduled appointments, female sex, and type of insurance predicted nonadherence to screening colonoscopies.…”
Section: Discussionsupporting
confidence: 74%
“…However, some researchers have suggested that obesity is a potential barrier for screening compliance and effectiveness. 41–44 In contrast, other studies have shown no effect of obesity on screening compliance 45 and have reported that mammography use and accuracy are not the reasons for the higher clinical stage in obese patients. 46 Moreover, another study reported that obese women had higher sensitivity for screening mammography with similar specificity, regardless of their BMI group.…”
Section: Discussionmentioning
confidence: 95%
“… 14 , 42 However, similar to our findings, an analysis using the 2016 BRFSS found no association between obesity and adherence to breast cancer screening. 43 …”
Section: Discussionmentioning
confidence: 99%